1999
DOI: 10.1074/jbc.274.35.24930
|View full text |Cite
|
Sign up to set email alerts
|

Activated Neutrophils Induce Hyperpermeability and Phosphorylation of Adherens Junction Proteins in Coronary Venular Endothelial Cells

Abstract: The endothelial adherens junction is formed by complexes of transmembrane adhesive proteins, of which ␤-catenin is known to connect the junctional protein vascular endothelial (VE)-cadherin to the cytoskeleton and to play a signaling role in the regulation of junctioncytoskeleton interaction. In this study, we investigated the effect of neutrophil activation on endothelial monolayer integrity and on ␤-catenin and VE-cadherin modification. Treatment of cultured bovine coronary endothelial monolayers with C5a-ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
139
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(144 citation statements)
references
References 28 publications
5
139
0
Order By: Relevance
“…E-selectin-induced activation of p38 regulates transendothelial permeability and migration of cancer cells by mediating the formation of stress fibres The formation of stress fibres in endothelial cells is associated with an increased retraction of the cells and with a subsequent increase in interendothelial gaps and permeability (Saito et al, 1998;Tinsley et al, 1999). We have previously shown that formation of stress fibres in response to oxidative stress and vascular endothelial growth factor (VEGF) is tightly associated with the activation of p38 Rousseau et al, 1997;Lamalice et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…E-selectin-induced activation of p38 regulates transendothelial permeability and migration of cancer cells by mediating the formation of stress fibres The formation of stress fibres in endothelial cells is associated with an increased retraction of the cells and with a subsequent increase in interendothelial gaps and permeability (Saito et al, 1998;Tinsley et al, 1999). We have previously shown that formation of stress fibres in response to oxidative stress and vascular endothelial growth factor (VEGF) is tightly associated with the activation of p38 Rousseau et al, 1997;Lamalice et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it was reported that coincubation of EC and C5a-activated neutrophils causes increased tyrosine phosphorylation of AJ proteins; however, the specific mechanisms of leukocyte-induced modification of AJ proteins remain unclear (26,27). To examine specifically the consequences of leukocyte binding to EC on the phosphorylation of VE-cadherin, we treated EC with TNF-␣, which has been shown to increase expression of cell adhesion molecules such as ICAM-1 and VCAM-1 (28).…”
Section: Leukocyte Adhesion To Ec Induces Tyrosine Phosphorylation Ofmentioning
confidence: 99%
“…An additional binding partner, p120, is thought to be involved in the control over membrane-localized cadherin turnover and stability [Komarova et al, 2007]. The adhesiveness of adherence junctions seems to be strongly regulated by tyrosine phosphorylation [Tinsley et al, 1999;Weis et al, 2004;Vestweber, 2007]; established vascular barrier disruptors histamine, VEGF and TNFα increase tyrosine phosphorylation of one or more proteins within adherence junctions [Angelini et al, 2006;Andriopoulou et al, 1999;Esser et al, 1998]. The phosphorylation was attributed to several tyrosine protein kinases, including Src, Fyn, Yes and Pyk2 [Lambeng et al, 2005;van Buul et al, 2005;Gong et al, 2008].…”
Section: Adhesion Complexes and Increased Transendothelial Permeabilitymentioning
confidence: 99%